Dual-energy computed-tomography cholangiography in potential donors for living-related liver transplantation: initial experience - Sommer, Christof-Matthias; Schwarzwälder, Christoph Bernhard; Stiller, Wolfram; Schindera, Sebastian Tobias; Heye, Tobias; Stampfl, Ulrike; Ramsauer, Stefanie; Bellemann, Nadine; Weitz, Jürgen; Schmidt, Jan; Grenacher, Lars; Kauczor, Hans-Ulrich; et al. (Investigative radiology, 2010)
Objectives: - To report our initial experience with dual-energy computed-tomography (CT) cholangiography in potential donors for living-related liver transplantation. - Materials and Methods: - Seventeen potential donors for living-related liver transplantation (6 women and 11 men; average age 37.8 ± 10.4 years) underwent contrast-enhanced dual-energy CT cholangiography. A dual-energy CT scan of the liver was carried out with acquisition of 2 raw datasets at tube currents of 140 and 80 kV, respectively. A third weighted average dataset were obtained (weighting ratio: 70% 140 kV, 30% 80 kV). Pure iodine images (fourth dataset) and contrast-optimized images (fifth dataset) were reconstructed. Analysis of all datasets comprised determination of bile duct visualization scores (on a scale of 1 to 4: 1, not visualized; 2, faintly seen; 3, identified but the origin or portions of the duct are not visualized; and 4, excellent visualization from origin to branches), maximum bile duct diameters, bile duct attenuation, and liver parenchyma attenuation as well as image noise, signal-to-noise ratio, and contrast-to-noise ratio. - Results: - Highest maximum bile duct diameters were detected for optimized-contrast images and the 80 kV dataset, intermediate for pure iodine images and the weighted average dataset and lowest for the 140 kV dataset with significant differences. Highest bile duct attenuation was detected for optimized-contrast images (535.7 ± 148.3 HU) and the 80 kV dataset (533.7 ± 145.9 HU) with significant differences compared with pure iodine images (344.9 ± 106.5 HU) and the weighted average dataset (355.5 ± 87.6 HU) (P < 0.001). Highest image noise was detected for the 80 kV dataset (39.3 ± 5.4 HU) with significant differences compared with the optimized-contrast images (31.5 ± 4.0) (P < 0.001). Highest signal-to-noise ratio and contrast-to-noise ratio were detected for pure iodine images (18.3 ± 7.1 and 17.6 ± 7.0) and optimized-contrast images (17.3 ± 5.8 and 14.8 ± 5.5) with significant differences compared with the 80 kV dataset (14.0 ± 5.2 and 11.8 ± 4.8) and the weighted average dataset (15.1 ± 4.4 and 12.1 ± 4.1) (P < 0.001 and P < 0.01). - Conclusions: - Dual-energy CT cholangiography in potential donors for living-related liver transplantation is remarkable. Pure iodine images and contrast-optimized images allow precise analysis of the biliary system with increased image quality compared with conventional images. Contrast-optimized images should be used for detection and localization of the bile ducts and pure iodine images for quantitative description of the anatomic dimensions of the biliary segments.